Maternal Health Out-of-Pocket Expenditure and Service Readiness in Lao PDR : Evidence for the National Free Maternal and Child Health Policy from a Household and Health Center Survey - World Bank (Washington, DC, 2014)
Although Lao PDR has made notable progress in improving maternal and child health (MCH), attainment of the Millennium Development Goal 5 (MDG5) still remains a challenge. This is largely due to the barriers imposed by financial restrictions. In order to address these financial barriers, the Government of Lao PDR has introduced a national free MCH policy. However, certain non-financial barriers are also impediments to the achievement of this goal, such as physical access to remote communities, especially during rainy season, cultural practices and beliefs, and poor educational outcomes. In seeking to inform the implementation and scale-up of this national free MCH policy at this crucial initial stage, this paper reports on findings from a household, village and health center survey The policy implications of the findings from the survey are: 1) although financial protection implied by the national free MCH policy is strong, reducing financial barriers alone would not be sufficient to increase the utilization of services, 2) this policy has the potential to be regressive due to the higher utilization of MH services by wealthier households, 3) health providers at all levels of health facilities would experience substantial marginal decreases in revenue, given the reimbursement schedules under the national free MCH policy, and 4) the supply-side readiness and management capacity of health centers needs to be improved. This paper is organized to present the background context, analyses, the equity of MH service utilization, the supply-side perspective, and key findings and recommendations.